BEYOND THE SCREEN: THE RETCONNING OF BLACK CHARACTERS IN POPULAR CULTURE MOVIES THROUGH THE LENS OF BLACKWASHING - Lu'lu'a, Lu'lu'a; Asysyamil, Muhammad Fikri; Zain, Ahsan; Hanif, Dzulfikar; Ros, Gerry; Pratama, Rizky Viko (UIN Raden Mas Said Surakarta, 2024)
The portrayal and adaptation of characters in movies often reflect societal norms and values, with